(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article discusses the problems and aspects of implementation of the national idea of Kazakhstan. Also raises questions about the mechanisms of implementation of the national idea and its features. This principles, which should guide the government in the implementation of the national idea. National idea – it is an idea common for all people of the country, stimulating and basic idea for all, united by the same slogan. Also this article considers some problems and scientific aspects of creating nationwide and idea of Kazakhstani state. Study of the problem of the national idea in the state is one of the controversial topics in contemporary political science. Denotes the relevance of the national idea in a multiethnic state like the Republic of Kazakhstan. The features and interests ethno groups that foster the advancement of the national idea. Key words: national idea, ideology, ethnos, patriotism, government.